Phosphorus speciation in water and sediments - Magdalena Matula; Małgorzata Wojtkowska (Desalination and Water Treatment)
Phosphorus is an important component of surface water environments. The paper describes phosphorus speciation and factors influencing this phenomenon. A detailed description concerned the cycles of phosphorus transformations in the aquatic environment in relation to phosphorus speciation. Samples of water and bottom sediments along the entire length of the Służewiecki Stream and from 7 adjacent ponds were collected and then analyzed. The paper presents the results of seasonal changes in the concentrations of phosphorus forms in the water column and bottom sediments in the Służewiecki Stream. Analytical and numerical methods were used to determine the potential forms of phosphorus in water and bottom sediments. In the water column, three phosphorus forms were determined: orthophosphates, polyphosphates, and the organic form of phosphorus. In bottom sediments, phosphorus forms were analyzed using Psenner's sequential extraction scheme. The concentrations of phosphorus forms were related to water quality and the composition of bottom sediments. The presence of mineral forms of phosphorus in water was modeled using the PHREEQC program, which used physico-chemical parameters of water quality. The influence of parameters such as: temperature, pH, and concentrations of O2, calcium, iron, and aluminum ions, on the transformations of mineral forms of phosphorus in the aquatic environment was described. The results of research on chemical indicators of water quality confirm their influence on the distribution of phosphorus forms in surface waters. The stream sediments were particularly rich in phosphorus adsorbed on metal oxides, which can be released due to changes in pH. Organic phosphorus, sourced from benthic bacteria and allochthonous material, was also recognized as a significant reservoir of phosphorus in water and bottom sediments The obtained results also showed that oxygen deficits occurring during the lakes surface ice coverage result in the release of significant amounts of polyphosphates into the water column. In bottom sediments, a significant amount of phosphorus bound with the apatite fraction was also found. Active release of phosphorus from this apatit-bound fraction has been associated primarily with the cyclical increase in air temperature, which determines the water temperature in lowland streams and shallow polymictic reservoirs. The study demonstrated significant transformations of phosphorus forms in the water-sediment system in reservoirs and watercourses located in areas of high anthropopressure.